Strategies to Engage 4-H Parents - Julia S. Kelly (EDIS)
Parent engagement makes a significant impact on a 4-H club’s success in fostering the development of targeted life skills in youth participants. This new 4-page publication of the UF/IFAS 4-H Youth Development Program presents 13 concrete strategies for engaging with parents and also addresses some potential challenges with communicating with parents. Written by Julia S. Kelly. https://edis.ifas.ufl.edu/4h430